Association between serum inflammatory parameters and the disease severity in COVID‐19 patients. Issue 1 (7th December 2021) - Mardani, Rajab; namavar, Mehrnoush; ghorbi, Elham; Shoja, Zabihollah; Zali, Fatemeh; Kaghazian, Hooman; Aghasadeghi, Mohammad Reza; Sadeghi, Seyed Amir; Sabeti, Shahram; Darazam, Ilad Alavi; Ahmadi, Nayebali; Mousavi‐Nasab, Seyed Dawood
Abstract: Objective: Most patients infected with the novel coronavirus (SARS‐CoV‐2), as the causative agent of COVID‐19 disease, show mild symptoms, but some of them develop severe illness. The purpose of this study was to analyze the blood markers of COVID‐19 patients and to investigate the correlation between serum inflammatory cytokines and the disease severity. Methods: In this prospective cross‐sectional study, 50 patients with COVID‐19 and 20 patients without COVID‐19 were enrolled. According to ICU admission criteria, patients were divided into two groups of non‐severe and severe. Differences in the serum levels of C‐reactive protein (CRP), IL‐6, and TNF‐α, as well as erythrocyte sedimentation rate (ESR), lymphocytes (LYM) count, and neutrophils (NEU) count between the two groups were determined and analyzed. Results: Out of the 50 patients with COVID‐19, 14 were diagnosed as severe cases. There was no significant difference between the two groups of COVID‐19 patients in terms of gender and age. Blood tests of COVID‐19 patients showed a significant decrease and increase in NEU and LYM counts, respectively. There were significant differences in the serum levels of IL‐6, TNF‐α, and CRP between the severe and non‐severe groups, which were higher in the severe group. Also, there was a significant correlation between the disease severity and CRP with ESR ( r  = 0.79), CRP with IL‐6 ( r  = 0.74), LYM with NEU ( r  = −0.97), and ESR with TNF‐α ( r  = 0.7). Conclusion: The findings of this study, as the first study in Iran, suggest that the levels of IL‐6, TNF‐α, ESR, and CRP could be used to predict the severity of COVID‐19 disease. Abstract : Serum inflammatory parameters were analyzed in patients with severe and non‐severe COVID‐19. The serum levels of LYM, CRP, IL‐6, TNF‐α and ESR in severe patients were significantly higher than in non‐severe patients. Measurement of inflammatory markers might help clinicians monitor and evaluate the severity and prognosis of COVID‐19.